Application Of Si-Izol (Online Licensing Information System) In Licensing Services At The Disnaker Pmptsp Of Malang City - Yasmin Nur Kholisa; Lukman Arif (UNIVERSITAS PAKUAN, 2025)
To improve the quality of public services, the government continues to enhance service delivery through innovations such as electronic government (e-government). One regional agency that has implemented e-government to improve licensing services is the Department of Manpower, Investment, and One-Stop Integrated Services (Disnaker PMPTSP) of Malang City. Currently, licensing services are provided online through the SI-IZOL Application. This study aims to analyze and describe the implementation of SI-IZOL in licensing services at Disnaker PMPTSP Malang City, using a qualitative method with a descriptive approach. Data were collected through interviews, observations, and documentation. The analysis framework is based on the success elements of e-government proposed by Harvard’s JFK School of Government: support, capacity, and value. The results of the study indicate that the implementation of the SI-IZOL application at Disnaker PMPTSP Malang City can be explained as follows:1) is reflected in Disnaker PMPTSP’s vision and mission, supporting regulations, collaboration with other parties, and public socialization efforts; 2) includes adequate financial resources, complete information technology infrastructure, and available human resources, although the latter remains less than optimal; 3) Value, the benefits experienced by Disnaker PMPTSP Malang City include more effective, efficient, and transparent licensing services. Similarly, the public benefits from faster services, reduced costs, and the convenience of accessing services anytime and anywhere. Overall, the SI-IZOL Application has contributed significantly to improving licensing services at Disnaker PMPTSP Malang City.